Clinical and functional features of the eyes with phakic lenses before and after bilensectomy - Marshava, D.O. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Implantation of phakic intraocular lens (PIOL) is used for high ametropia correction. The insufficiency of PIOL implantation is the development of cataract in the remote terms after surgery due to the contact of constructive elements of PIOL to anterior and posterior eye chamber tissues. The purpose of the present paper was to study clinical and functional features of the eyes with PIOL before and after performing BEC. Material and Methods. 25 eyes of 19 patients with various PIOL models were compared before and after bilensectomy. Results. We confirmed the difference in the character of cataracts developed after implantation of pupil-fixated (Pf) and posterior chamber (PC)PIOLs from cataracts developed after implantation of anterior chamber lens with posterior chamber fixation (ACPCf). There were three degrees of eye reaction after BEC depending on the type of removed PIOL. Conclusions. The course of intra- and postoperative period in BEC depends on pre-existing alterations in the eye. Discordance between a cataract process clinical picture and a PIOL type is an indication for deep investigation of patients.